A geological evaluation of marine diamond placer deposits on the central Namibian inner shelf : a case study of the Hottentot Bay area - Rau, Grant (Rhodes University, Faculty of Science, Department of Geology, 2004)
This study focusses on the marine diamond placers within Exclusive Prospecting Licence 1950 and Mining Licence 103a, located northwest of the north-facing Hottentot Bay which is 60 km north of Lüderitz, along the central Namibian coastline. The thesis follows the natural geological evolution of the marine placer deposit from primary source, through alluvial and/or glacial transportation, concentration along the coastline by wave, aeolian and alluvial/sheet-wash processes and finally marine diamond placer preservation. All of these processes are reviewed as they are important in understanding of the evolution marine placer deposits. The poly-cyclic role of coastal aeolian, alluvial, and marine processes, in marine placer enrichment is shown to be particularly important in considered target identification and prioritisation. A detailed bathymetric, sonographic and seismic interpretation, is an integral part of diamond placer exploration, and was used to examine and describe surficial and sub-bottom characteristics within the study area. Marine placers are formed along palaeo-strandlines during periods of marine transgression and regression and are therefore fundamental in marine placer exploration. A detailed bathymetry map, compiled for this study, of the area between Lüderitz Bay and Clara Hill, provides the foundation for a detailed terrace level investigation. Regionally, twelve well-developed stillstand levels are identified, nine of which fall into the study area. These interpretations are compared with global eustatic as well as terrace and resource/reserve levels in the Lüderitz area and are found to correlate well. Sediment dynamic studies involve the use of accredited application software for wave refraction modelling, to determine the wave angle and orbital wave velocity at the seabed. Bedload velocities, required to move diamonds of specific sizes, can be empirically determined and therefore areas of diamond entrainment and deposition can be modelled and target features delineated and prioritised. These detailed interpretations provide a sound platform for evaluating diamond placer process models in the study area. By integrating both previously published and newly formulated ideas, a revised, holistic model for the formation of marine diamond placer deposits in central Namibian is postulated. The proposed model is tested by comparing it to the lateral distribution of presently defined resource/reserve areas in the Lüderitz area and shows a close correlation with most of these enriched deposits. Based on this model, a matrix for the delineation and prioritisation of marine placer deposits is developed and the best target features within the study area are identified.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Diamond mines and mining -- Namibia; Ocean mining -- Namibia; Marine mineral resources